Kajian Penerapan Konsep Lingkungan Restoratif pada Bangunan Masjid 99 Kubah di Makassar - Mustajab Aras, Adnan; Syuaib, Mayyadah; Masardy Tahir , Andhy; Uniarti Ananda, Ovy; Maulana Muharram, Ikrar (The Department of Architecture, Faculty of Science and Technology, Alauddin Islamic University of Makassar, 2022)
This study aims to determine the object of research applying the criteria as a restorative environment. The object of this study is the 99-domes mosque located in the central Point of Indonesia (CPI) Tanjung Bunga Makassar. The method used is descriptive analysis method, which is by collecting data and comparative studies and then analyzed and concluded. In collecting data, conducted several ways such as literature studies to obtain relevant data and references, then interviews, as well as field observations to directly feel the atmosphere of the object to be discussed. The results showed that the existence of this mosque can give the community a restorative experience. The experience of calm and peace from to these criteria has managed to restore the physical and psychological condition of the people. It can be said that visitors regain their energy and motivation to undergo the next activity.